MANAGEMENT AND OUTCOMES OF INCIDENTAL MENINGIOMAS: IS ROUTINE FOLLOW-UP REQUIRED?. (3rd October 2018) - Islim, Abdurrahman; Rathi, Nitika; Mills, Samantha; Brodbelt, Andrew R; Jenkinson, Michael
Abstract: BACKGROUND: 30% of newly-diagnosed meningiomas are incidental findings. There is no consensus on the optimal management of these patients. OBJECTIVE: To determine the clinical outcomes of patients diagnosed with incidental meningioma. METHODS: Single centre retrospective cohort study of patients diagnosed with an incidental meningioma between 2007 and 2015. RESULTS: 441 patients were included (459 meningiomas). Mean age at diagnosis was 63.3 years (range: 19–97); 348 female and 93 male. The main indication for MRI/CT was headache (25.9%). Median meningioma volume at diagnosis was 1.58 cm 3 range: 0.06–51.8). Commonest location was convexity (39.9%). At initial presentation, 6 patients underwent surgical resection, 50 were discharged and the remaining 385 entered surveillance imaging (1303 scans in total, 3.4 on average over a median of 36 months [range: 3–120]). Overall outcomes by the end of the study period were: 219 discharged, 12 lost to follow-up, 4 deaths (unrelated to their meningiomas) and 206 under continued observation. Of those 206, 38 (18.4%) (mean age: 52.9 years) had intervention (34 surgery, 2 stereotactic radiosurgery, 2 fractionated radiotherapy) after a median follow-up period of 24 months (range: 3–78). Indications for treatment were radiological progression (n=26), development of symptoms (n=6), and patient preference (n=6). Pathology revealed WHO grade I (benign) in 36 patients and WHO grade II (atypical) in 4 patients, of which one had recurrence 5 months after surgery and required salvage radiotherapy. For 231 patients discharged/lost to follow-up (mean age: 68.1 years), median follow-up duration was 18 months (range: 0–120). Nine patients (3.9%) had further MRI/CT for unrelated symptoms after a median of 37 months. CONCLUSION: The majority of incidental meningiomas do not require long-term follow-up and our data suggests that a 5-year period is sufficient. Further analyses of clinical and radiological predictors of growth and subsequent intervention are planned.